Sertraline exerts its antitumor functions through both apoptosis and autophagy pathways in acute myeloid leukemia cells. Issue 9 (2nd September 2017) - Xia, Di; Zhang, Ying-Ting; Xu, Gui-Ping; Yan, Wei-Wei; Pan, Xiao-Rong; Tong, Jian-Hua
Abstract: It has been found that sertraline, a widely used antidepressant drug, possessed antitumor roles in a variety of cancers including liver cancer, colorectal cancer and lymphoma. In this study, we provided evidences that sertraline had potent antiproliferative activity not only in acute myeloid leukemia (AML) cell lines but also in the fresh leukemia cells from AML patients, and could induce cell death through both apoptosis and autophagy pathways. Moreover, we found that inhibiting autophagy pathway could partially attenuate sertraline-induced apoptosis and cell growth inhibition, indicating that sertraline-induced autophagy process could facilitate AML cell apoptosis to some degree. However, blocking apoptosis pathway seemed no obvious effects on sertraline-caused autophagy as well as cell growth inhibition. Our results suggested a potential application value of sertraline in the treatment of AML patients, furnishing some perspectives for novel therapeutic strategies in leukemia.